2014
DOI: 10.5114/aoms.2014.44872
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research Effects of ghrelin on protein expression of antioxidative enzymes and iNOS in the rat liver

Abstract: IntroductionWe investigated the effects of ghrelin on protein expression of the liver antioxidant enzymes superoxide dismutases (SODs), catalase (CAT), glutathione peroxidase (GPx), and glutathione reductase (GR), nuclear factor κB (NFκB) and inducible nitric oxide synthase (iNOS). Furthermore, we aimed to investigate whether extracellular regulated protein kinase (ERK1/2) and protein kinase B (Akt) are involved in ghrelin-regulated liver antioxidant enzymes and iNOS protein expression.Material and methodsMale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 85 publications
(104 reference statements)
2
23
0
1
Order By: Relevance
“…Animal studies have shown that altered hepatic lipid metabolism interferes with activation of inflammatory signaling pathways, leading to upregulation of iNOS and alteration of IRS/PI3K/Akt insulin signaling pathway and consequent hepatic IR and injury as shown by us [29] and others [18,[64][65][66]. Clinical trials have shown similar results and indicate that excessive lipid accumulation triggers an immune system response through proinflammatory cytokines, leading to increased iNOS activation and development of inflammation, oxidative damage and IR [41,46,83,89].…”
Section: Evidence From Clinical Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…Animal studies have shown that altered hepatic lipid metabolism interferes with activation of inflammatory signaling pathways, leading to upregulation of iNOS and alteration of IRS/PI3K/Akt insulin signaling pathway and consequent hepatic IR and injury as shown by us [29] and others [18,[64][65][66]. Clinical trials have shown similar results and indicate that excessive lipid accumulation triggers an immune system response through proinflammatory cytokines, leading to increased iNOS activation and development of inflammation, oxidative damage and IR [41,46,83,89].…”
Section: Evidence From Clinical Studiessupporting
confidence: 52%
“…It is biosynthesized by three distinct isoforms of NOS enzyme: nNOS, eNOS and iNOS [10,26]. All three isoforms of NOS enzyme are expressed in the liver [27], but unlike eNOS and nNOS, which are constitutively expressed in physiological condition, iNOS is expressed when stimulated by different factors including inflammation and oxidative stress [11,[28][29]. Once expressed iNOS may generate large amounts of NO over long period of time [30].…”
Section: Hepatic Inos and Nomentioning
confidence: 99%
“…Ghrelin promotes an antioxidative defense mechanism in the rat liver, not only by reducing the NF-B protein levels but also by increasing the protein expression of antioxidative enzymes (e.g., superoxide dismutase, catalase, and GSH peroxidase) [17]. Accordingly, in the present study, suppression of NF-B activation by ghrelin or obestatin during mesenteric I/R also enhanced the antioxidant content of both the ileal and pulmonary tissues and protected them against injury.…”
Section: Discussionmentioning
confidence: 72%
“…There are limited studies referring to a relationship between ghrelin and oxidative stress enzymes in liver. Dobutovic et al (2014) reported that ghrelin stimulation increased antioxidative enzymes in rat liver. We also evaluated oxidative stress markers and anti-oxidants in STZ-diabetic and ghrelin-treated rat livers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ghrelin has antioxidant effects and stimulates the liver antioxidative proteins. It is known that increased oxidative stress plays a major role in the development and progression of diabetes (Dobutovic et al, ). Therefore, the purpose of the present study was to investigate antiapoptotic, cell proliferative and antioxidative effects of ghrelin administration in the liver of diabetic rats.…”
Section: Introductionmentioning
confidence: 99%